2013
DOI: 10.1590/s0100-06832013000600023
|View full text |Cite
|
Sign up to set email alerts
|

Upland rice under no-tillage preceded by crops for soil cover and nitrogen fertilization

Abstract: SUMMARYThe grain yield of upland rice under no-tillage has been unsatisfactory and one reason could be the nitrate/ammonium balance in the soil. Cover crops and nitrogen fertilization can be used to change the nitrate/ammonium relation in the soil and improve conditions for the development of upland rice in the no-tillage (NT) system. The aim was to study the effect of cover crops and nitrogen sources on grain yield of upland rice under no tillage. The study was carried out on the Fazenda Experimental Lageado,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Upland rice cultivation has lower water consumption requirements and is compatible with current agricultural production practices in subsistence crop systems, with few purchased inputs to high-technology systems needed (Kumar and Ladha 2011; Crusciol et al 2013). Studies have reported grain yields of rainfed upland rice of greater than 3 Mg ha -1 (Moro et al 2013;Nascente and Stone 2018). Upland rice cultivation has been used to convert raw land to agriculture, to quickly renew degraded pasture in one growing season, and in rotation with soybean [Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upland rice cultivation has lower water consumption requirements and is compatible with current agricultural production practices in subsistence crop systems, with few purchased inputs to high-technology systems needed (Kumar and Ladha 2011; Crusciol et al 2013). Studies have reported grain yields of rainfed upland rice of greater than 3 Mg ha -1 (Moro et al 2013;Nascente and Stone 2018). Upland rice cultivation has been used to convert raw land to agriculture, to quickly renew degraded pasture in one growing season, and in rotation with soybean [Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving soil fertility and increasing the yield of the subsequent crop (Crusciol et al 2015), these perennial forage grasses reduce potential losses from leaching due to their deep roots (Sullivan et al 2017). Moro et al (2013) obtained maximum grain yields of 4.8-6.8 Mg ha -1 for rainfed upland rice grown in succession to Urochloa grasses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen is one of the most dynamic nutrients in the soil (MORO et al, 2013;NASCENTE et al, 2014). However, the low efficiency of the agronomical use of this nutrient, observed in most agricultural systems, is the result, in part, of losses associated with nitrification of N, i.e., N losses by leaching and denitrification of N-NO 3…”
Section: Introductionmentioning
confidence: 99%
“…These modifications include the addition of acidic products (BREMNER;DOUGLAS, 1971) and the production of fertilizers with solubility controlled by means of resins or polymers or even elemental sulfur cover (GOULD et al, 1986;FANSURI et al, 2008;CIVARDI et al, 2011;MORO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%